Cross species amplification and characterization of microsatellite markers in leporinus friderici (Characiformes, anostomidae) - Utsunomia, Ricardo; Foresti, Fausto [UNESP]; Porto-Foresti, Fábio [UNESP]; da Silva, Caio Felipe [UNESP]; Martins, Diego Galetti [UNESP]; Prado, Fernanda Dotti Do [UNESP] (FapUNIFESP (SciELO), 2021)
Leporinus friderici is a migratory neotropical fish with elevated ecological and economic importance in Brazil. Microsatellite markers are highly important in population genetic studies, management, and conservation programs; however, no markers are available for this species. In this study, seven microsatellite loci, previously developed for Megaleporinus obtusidens, were successfully cross-amplified in L. friderici. Among these loci, five presented moderate to high genetic variability levels, with four to seven alleles per loci and expected heterozygosities varying from ≥ 0.574 to 1.000. These markers represent a valuable tool for the future management and ecological studies involving this species and group of neotropical fishes.
Amplificação cruzada e caracterização de marcadores microssatélites em leporinus friderici (Characiformes, anostomidae)
Keywords: Fish genetics; Genetic conservation; Molecular markers; Neotropical fish